Real-world treatment patterns of patients with acute coronary syndrome based on 15-year data - Inga S. Egorova; Natalia N. Vezikova (КардиоСоматика)
BACKGROUND: About half a million cases of acute coronary syndrome (ACS) are diagnosed in Russia every year. However, despite optimized treatment of patients with ACS, mortality remains high, which dictates the need to analyze the effectiveness of therapeutic measures.